Antibody response against selected epitopes in the HIV-1 envelope gp41 ectodomain contributes to reduce viral burden in HIV-1 infected patients - Rute Marcelino; Filipa Gramacho; Francisco Martin; Pedro Brogueira; Nuno Janeiro; Claudia Afonso; Robert Badura; Emília Valadas; Kamal Mansinho; Luís Caldeira; Nuno Taveira; José M. Marcelino (Scientific Reports, 2021)
Abstract The ectodomain of gp41 is the target of potent binding and neutralizing antibodies (NAbs) and is being explored in new strategies for antibody-based HIV vaccines. Previous studies have suggested that the W164A-3S (3S) and EC26-2A4 (EC26) peptides located in the gp41 ectodomain may be potential HIV vaccine candidates. We assessed 3S- and EC26-specific binding antibody responses and related neutralizing activity in a large panel of chronic HIV-1-infected Portuguese individuals on ART. A similar proportion of participants had antibodies binding to 3S (9.6%) and EC26 (9.9%) peptides but the level of reactivity against 3S was significantly higher compared to EC26, except in the rare patients with double peptide reactivity. The higher antigenicity of 3S was unrelated with disease stage, as assessed by CD4+ T cell counts, but it was directly related with plasma viral load. Most patients that were tested (89.9%, N = 268) showed tier 1 neutralizing activity, the potency being inversely associated with plasma viral load. In the subset of patients that were tested for neutralization of tier 2 isolates, neutralization breadth was inversely correlated with plasma viral load and directly correlated with CD4+ T cell counts. These results are consistent with a role for neutralizing antibodies in controlling viral replication and preventing the decline of CD4+ T lymphocytes. Importantly, in patients with 3S-specific antibodies, neutralizing titers were inversely correlated with viral RNA levels and proviral DNA levels. Moreover, patients with 3S and/or EC26-specific antibodies showed a 1.9-fold higher tier 2 neutralization score than patients without antibodies suggesting that 3S and/or EC26-specific antibodies contribute to neutralization breadth and potency in HIV-1 infected patients. Overall, these results suggest that antibodies targeting the S3 and EC26 epitopes may contribute to reduce viral burden and provide further support for the inclusion of 3S and EC26 epitopes in HIV-1 vaccine candidates.